Struktur Agroforestri Kakao Muda dan Penerimaan Petani di Desa Sidomulyo Kecamatan Air Naningan, Tanggamus - Evizal, Rusdi; Prasmatiwi, Fembriarti Erry (Universitas Lampung, 2023)
The successful adaptation of cocoa clones from Sulawesi in Lampung Province, especially since the release of the MCC clone in 2015, has increased farmers' interest in rehabilitating cocoa plantations, carrying out cloning and replanting using these superior clones. This study aims to study the structure of young cocoa agroforestry vegetation and farmer income in Air Naningan District, Tanggamus Regency.The research was conducted using a survey method. The sample agroforestry gardens selected purposively as models were young agroforests with complex vegetation structures and agroforests with simple vegetation structures. The results of this study indicate that the rehabilitated young cocoa-based agroforestry vegetation structure is affected by the previous tree stands. In addition, the vegetation is dominated by banana plants as productive shade so that the main crops are cocoa and bananas. In complex agroforestry systems, more types of associated crops are found than in simple agroforestry systems. Important structures as characteristics of young cocoa agroforestry are young interplanting which will later become the main crops, namely cocoa, coffee and avocado. In addition, in complex agroforestry types, tree structures with stump sprouts (regrowth trees) are found which are often pruned as goat fodder. In both types of agroforestry, various types of understorey crops were found from the food crop group, vegetables, fruit, and spices. Weekly revenue for rehabilitated cocoa-based agroforestry come from cocoa and banana yields. Palm sugar (Arenga pinnata) production is an important source of daily revenue for agroforestry farmers who manage palm trees. Key words : Agroforestry, Arenga, banana, cacao, coffee, rubber, rehabilitation, revenue, taro